2006
DOI: 10.1097/01.bpo.0000203016.96647.43
|View full text |Cite
|
Sign up to set email alerts
|

Function and Upright Time Following Limb Salvage, Amputation, and Rotationplasty for Pediatric Sarcoma of Bone

Abstract: We wished to determine the relative physical and psychosocial merits of limb-sparing reconstruction, above-knee amputation, and rotationplasty in survivors of childhood and adolescent lower extremity bone sarcoma. In comparing minimum 5-year disease-free survivors, we found that outcome was somewhat dependent on the measuring tool administered. A superior score of statistical significance on the system of evaluation of the Musculoskeletal Tumour Society and a trend toward higher Toronto Extremity Salvage Score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
81
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 17 publications
9
81
0
Order By: Relevance
“…Among our original cohort only 39% of the potentially eligible patients 15 years or older were available for 1-year followup. Although this represents a limitation with a high risk of selection bias, it is generally similar to that of related retrospective series [15,28]. Second, to allow patients to reach a functional plateau, a minimum followup of 1 year was set.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among our original cohort only 39% of the potentially eligible patients 15 years or older were available for 1-year followup. Although this represents a limitation with a high risk of selection bias, it is generally similar to that of related retrospective series [15,28]. Second, to allow patients to reach a functional plateau, a minimum followup of 1 year was set.…”
Section: Discussionmentioning
confidence: 97%
“…This resulted in 527 English-language articles published from 1990 to present, from which 11 articles were identified that compared functional status of limb salvage with amputation (Table 3). Only one of 11 publications observed a difference in quality-of-life scores between the two groups [15]. Three publications included an objective, quantitative functional measure [4,10,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoprosthesis alternatives must be considered. Amputation and rotationplasty are alternatives to limb-preservation surgery [4,12,22,30]. These surgeries require the patient to use an external prosthesis for ambulation.…”
Section: Discussionmentioning
confidence: 99%
“…Today, rotationplasty is one option for surgical management of musculoskeletal tumors, particularly in children [2,3,8,18] or as a salvage option after failed reconstruction [4,5,13]. Overall function reportedly is excellent [4,10,15]. There have been no problems with wound healing.…”
Section: Introductionmentioning
confidence: 99%